Study of pattern of lipid profile amongst type II diabetic patients of two major tribal populations of Tripura - Sagar Samrat Debbarma; Arunabha Dasgupta; Atanu Ghosh; Kanak Choudhury; Prithvijit Kole; Sonali Paul; Brainist Kalai; V. Saikumar (Journal of Family Medicine and Primary Care)
Background: Diabetic population are at an increased risk of developing dyslipidemia and other cardiovascular complications. The study was performed to evaluate the lipid profile parameter in the diabetic population among the ethnic tribal community of Tripura and calculate the risk of cardiovascular events. The tribal community was chosen as the study population because their lifestyle, food habits, culture and housing practices are different from people living on the plains. There are 19 indigenous tribes and among them, two major tribes are the Tripuris and Reangs. These two communities were selected for the study. Aims and Objectives: To estimate the lipid profile parameters in the diabetic population of the two major tribal communities of Tripura and determine the correlations of lipid profile parameters with HbA1c. Methodology: The study was an observational analytical study. A total of 90 study subjects were selected by calculating the sample size and 90 controls were also chosen. All diabetic study subjects underwent lipid profile analysis along with other necessary investigations after having proper informed consent. Also, 90 controls had lipid profile analysis performed along with blood sugar estimation. Results: In this study, 63 subjects were from the Tripuri population and the rest 27 were from the Reang community. A total of 48 subjects were male and 42 were female. The mean age of the study population was 56.99 ± 9.97 years. Also, 31.1% of the study population was found to be having dyslipidemia and this finding was statistically significant. Risk calculation of dyslipidemia revealed that the diabetic population was 2.25 times more prone to developing dyslipidemia than the non-diabetic population. There was a positive correlation of HbA1c with low-density lipoprotein (LDL), serum triglyceride and serum cholesterol (TC) levels and these correlations were statistically significant. However, there was a negative correlation of HbA1c with high-density lipoproteins (HDL). Also, 75% of the study population was hypertensive and this finding was also statistically significant. Obesity was also an important risk factor and the association of BMI with HbA1c in the study population was statistically significant. Discussion: In all, 31.1% of the diabetic population amongst the two tribal communities was found to have dyslipidemia and this finding was statistically significant. Gender did not influence the development of dyslipidemia in diabetics and neither did the age of the study population. The duration of diabetes mellitus too had no statistically significant relationship. There exists a positive correlation of HbA1c values with LDL, triglycerides and cholesterol values indicating that uncontrolled DM is associated with dyslipidemia. HDL had a negative correlation. The ratio of TC/HDL and LDL/HDL showed that this study population is at a moderate risk of developing cardiovascular events. Also, 75% of the study population was hypertensive and risk calculation showed dyslipidemic subjects were 4.9 times more prone to developing hypertension and the calculation was statistically significant. Conclusion: The study on the tribal populations of Tripura revealed that uncontrolled DM is associated with high levels of LDL, triglycerides and cholesterol levels in spite of differences in food habits and lifestyle. Dyslipidemia is associated with hypertension. The study population is at a moderate risk for developing cardiovascular complications according to the Framingham Heart study.